Endovascular repair of a type B aortic dissection with a right-sided aortic arch: case report - Zhou Weimin (Journal of Cardiothoracic Surgery, 2013)
Abstract Right-sided aortic arch is a rare anomaly, and aortic dissection involving a right-sided aortic arch is extremely rare. We report the case of a 65-year-old man with a right-sided aortic arch and a right descending aortic dissection and a stent-graft was accurately deployed without perioperative complications. There were no any complaints and complications after 18 months follow-up. The CTA demonstrated that the false lumen was largely thrombosed only with a mild type II endoleak and a mild descending aortic expansion. We feel that endovascular repair is feasible to patient of type B aortic dissection with a right-sided aortic arch. However, long-term clinical efficacy and safety have yet to be confirmed.